2009
DOI: 10.1016/j.jneuroim.2008.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endotoxin and systemic immune activation in sporadic amyotrophic lateral sclerosis (sALS)

Abstract: The present study reports elevated levels of endotoxin/lipopolysaccharide (LPS) concentrations in plasma from patients with sporadic amyotrophic lateral sclerosis (sALS) and Alzheimer's (AD) as compared to healthy controls. Levels of plasma LPS showed a significant positive correlation with degree of blood monocyte/macrophage activation in disease groups and was most elevated in patients with advanced sALS disease. There was a significant negative relationship between plasma LPS and levels of monocyte/macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
205
4
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(221 citation statements)
references
References 34 publications
9
205
4
3
Order By: Relevance
“…Overall, many diseases of chronic inflammation may be attributed to the presence of microbial components such as LPSs [1,15,70]. The continuous generation of bacterial components, considered as potent inflammatory agents, as well as their feedback from the pool of the dormant bacteria, may well justify the persistent, but mild-manifested inflammation, followed by inflammatory cytokine production, which is characteristic of many diseases [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, many diseases of chronic inflammation may be attributed to the presence of microbial components such as LPSs [1,15,70]. The continuous generation of bacterial components, considered as potent inflammatory agents, as well as their feedback from the pool of the dormant bacteria, may well justify the persistent, but mild-manifested inflammation, followed by inflammatory cytokine production, which is characteristic of many diseases [20].…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of endotoxin LPSs in plasma from AD patients increased compared to controls. This increase was reflected in a proportionally-dependent degree of blood monocytes activation, which was positively associated with the genesis of AD [15]. Bacterial cells in the blood of AD patients in dormancy were visualized with ultrastructural microscopy: when iron deficiency has been overcome, it leads to their revivification [16].…”
Section: Introductionmentioning
confidence: 99%
“…So the levels of LPS in the blood represent not only inflammation but also leaky gut. Studies found that the plasma levels of LPS in patients with AD were three times higher than healthy controls (Zhang et al, 2009). LPS is usually used to create inflammation in laboratory animals.…”
Section: Leaky Gut Leaky Brain and Admentioning
confidence: 99%
“…Whether neuroinflammation is a cause or a consequence of motoneuron death is still debated. It is interesting to note that inflammation is not limited to the CNS but systemic with increased levels of plasma LPS associated with increased numbers of activated circulating monocytes and T lymphocytes that correlate with disease evolution [142,157]. A thymic dysfunction is also observed in parallel to the neurodegenerative process in mutant SOD1 mice and ALS patient [158].…”
Section: G93amentioning
confidence: 99%